Cost-effectiveness of telemedicine interventions: A systematic literature review - Dimvy Rusefani Asetya (Health Economics Insights Journal, 2026)
Telemedicine has expanded rapidly, accelerating during the COVID-19 pandemic; however, decision-makers require robust economic evidence to guide sustained investment and reimbursement. However, whether it represents value for money versus in-person care remains contested. To systematically identify, appraise, and synthesize full economic evaluations comparing telemedicine interventions with usual or in-person care and to summarize their cost-effectiveness across clinical domains. This systematic literature review was conducted and reported in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. PubMed/MEDLINE, Scopus, and Web of Science were searched from database inception to 31 October 2025. Eligible studies were full economic evaluations (cost-effectiveness, cost-utility, cost-benefit, or cost-minimization analyses) of telemedicine versus usual or in-person care, reporting incremental costs and consequences. Records were dual-screened, data were extracted in duplicate, and reporting quality was appraised against CHEERS 2022 and the Drummond framework. Heterogeneity precluded meta-analysis; therefore, a structured narrative synthesis was undertaken. Of the 3,311 records identified, 17 full economic evaluations (published 2007–2025; eight countries) met the inclusion criteria. The interventions included chronic disease telemonitoring and telerehabilitation, teleconsultation and specialist access, mental health teletherapy, and diagnostic or acute care telemedicine. The findings were mixed but frequently favorable: several teleconsultation, teledermatology, telestroke, and teletherapy interventions were cost-saving or dominant, whereas home telemonitoring for chronic disease was often not cost-effective at conventional thresholds. Cost-effectiveness was strongly context-dependent and driven by avoided travel, activity volume, and intervention delivery costs. Telemedicine can be cost-effective, but its value is conditional on modality, clinical context, and scale rather than universal.